Synthesis and Characterization of Date Palm Fiber-Based Bio-Char and Activated Carbon and its Utilization for Environmental Remediation - Nasir, Mohammad Ibrahim; Hossain, Md. Zakir; Charpentier, P. A. (Journal of Petroleum Research and Studies, 2018)
Natural agricultural products have the potential to be a substitute for synthetic polymers absorbents in environmental remediation and spill cleanup and recovery. One of these natural by-products which is available in many regions of the world is Date Palm Fibers (DPF). DPF (also known as surface fibers) is a natural sorbent that exhibits good sorption characteristics. In an attempt to valorize this abundant, low cost byproduct, we have investigated the micro porosity of this raw material by carrying out two procedures. First, hydrothermal pyrolysis using a scalable reactor with only water as solvent at high temperature (480 °C) under dry nitrogen atmosphere. Biochar yield was found varying from 30.5 to 33.6% (32%), with little bio-oil. Then the resultant biochar was physically activated with KOH and the mixture heated to 750oC (0.5oC/min) and kept at 750°C for 2 hours under Argon flow in a tubular furnace to produce activated carbon. Second, the resulting biochar and activated carbons were then characterized by Particle Analyzer to measure their surface area, pore volume and pore diameter. For biochar, surface area : 1.1374 m²/g, pore volume 0.001883 cm³/g, pore diameter 1355.874 Å and for activated biochar (activated carbon), surface area : 1220.2755 m²/g, pore volume: 0.062068 cm³/g, pore diameter: 19.0116 Å were determined by particle characterization analyzer. Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD) was also used for other analysis . The oil sorption behavior of the raw DPF, biochar and activated biochar were examined with motor oil. The Oil Sorption Capacity (OSC) of raw DPF, biochar and activated biochar were tested with the oil as oil alone and an oil over water surface and the value calculated gravimetrically. The maximum OSC values of the sorbents were in the order of: DPF<biochar< activated Biochar with OSC values of 8.952, 11.712 and 33.402 g*oil/g*sorbent, respectively at a sorption time of 30 min. That indicate the OSC of the sorbents above are proportional with its surface areas. The sorbent materials can be utilized in oil spill remediation as well as waste water treatment for removal of hydrocarbons pollutants from water. In addition biochar can be used as a soil amendmentfor enhancing soil fertility